Induction of remission in diabetes by lowering blood glucose - Weir, Gordon C.; Bonner-Weir, Susan (Frontiers in Endocrinology, 2023)
As diabetes continues to grow as major health problem, there has been great progress in understanding the important role of pancreatic beta-cells in its pathogenesis. Diabetes develops when the normal interplay between insulin secretion and the insulin sensitivity of target tissues is disrupted. With type 2 diabetes (T2D), glucose levels start to rise when beta-cells are unable to meet the demands of insulin resistance. For type 1 diabetes (T1D) glucose levels rise as beta-cells are killed off by autoimmunity. In both cases the increased glucose levels have a toxic effect on beta-cells. This process, called glucose toxicity, has a major inhibitory effect on insulin secretion. This beta-cell dysfunction can be reversed by therapies that reduce glucose levels. Thus, it is becoming increasingly apparent that an opportunity exists to produce a complete or partial remission for T2D, both of which will provide health benefit.